ChemInform Abstract: Elusive Metal‐Free Primary Amination of Arylboronic Acids: Synthetic Studies and Mechanism by Density Functional Theory. Issue 20 (25th April 2013) - Zhu, Chen; Li, Gongqiang; Ess, Daniel H.; Falck, John R.; Kuerti, Laszlo
Abstract A new, simple, and metal‐free method to prepare a wide a range of primary aromatic amines is reported.